ChemInform Abstract: Lewis Acid Catalyzed Cyclizations of Epoxidized Baylis—Hillman Products: A Straightforward Synthesis of Octahydrobenzo[e]azulenes. Issue 52 (10th December 2015) - Konopacki, Donald B.; Shortsleeves, Kelley C.; Turnbull, Mark M.; Wikaira, Jan L.; Hobson, Adrian D.
Abstract: The title azulene derivatives are obtained by a linear three‐step route involving the coupling of 2‐cyclopentenone with various aldehydes, stereoselective epoxidation, and Lewis acid catalyzed cyclization.